khalistresnafauzan Tingkat Motivasi Belajar Siswa Putriterhadap Pembelajaran Penjas Kelas VII SMPN 1 Kutawaluya - Khalis Tresna Fauzan; Rina Marlina; Muhammad Mury Syafei (Jurnal Ilmiah Wahana Pendidikan, 2022)
The level of motivation is low for female students, and incidents like this must be minimized, because we know that physical education is very important for everyone, to maintain a healthy body we must be diligent in exercising, and this sport can be triggered during physical education learning at school both in theory and in studies. practice. Therefore, this study aims to determine and analyze the level of learning motivation of female students when learning physical education for class VII SMPN 1 Kutawaluya. The research method used is descriptive quantitative. The population in this study involved all seventh grade female students with a sample of 100 female students at SMP Negeri 1 Kutawaluya. The data analysis technique was carried out descriptively through text analysis through a graphical display of the data. The results showed that the motivation of female students towards physical education lessons at SMP Negeri I Kutawaluya it can be concluded that female students who gave the answer "YES" with a frequency of 1321 and a percentage of 66.05% and female students who gave an answer "NO" with a frequency of 679 and a percentage 33.95% with sufficient overall criteria. Keywords: motivation level, female students.